Exploration of Teachers’ Role in Resource Class: A Case from an Integrated School - Sherpa, Dawa; Baraily, Khagendra (AMC Journal, 2021)
This study aimed at exploring the teacher’s role in resource class especially focusing on how resource teacher contributes to mainstreaming of children with disability. For this purpose, the researcher applied hermeneutics phenomenology as a research design. Five resource teachers from two integrated school from Kathmandu valley were selected as research participants by purposive sampling. The researchers adopted in depth interview and class observation to gather the rigorous information. Data analysis had been carried out along with the categorization of themes of collaboration, observation of activities of resource teachers and understanding of service delivery model. From the interview protocol the responses were transcribed and basic themes had been organized. Main themes were extracted from the basic themes. Main theme had been discussed with thematic network to draw final conclusion. The findings showed that the roles and responsibility of resource teachers are to support general teacher, to teach basic adaptive skills for children with the disability, creating collaborative environment with the parents and professionals. Therefore, the resource teacher’s roles to identification of need for children with disability, co-operation with parents and general teachers that contributes to transition planning in the individualized education plan. The findings provided implications that produced a plan to assist in the collaboration between the two educational environments.